2015
DOI: 10.7202/1027980ar
|View full text |Cite
|
Sign up to set email alerts
|

Migration adolescente et autonomie féminine en matière de divorce en Afrique : réflexions à partir d’un suivi de population au Mali

Abstract: Les migrations de travail des adolescentes se sont imposées comme un phénomène de masse et un déterminant des évolutions de l’entrée en union dans de nombreuses populations rurales ouest-africaines. Ont-elles aussi des retombées à plus long terme dans la gestion de la vie conjugale des femmes, notamment en matière de divorce ? La question est abordée à partir des données quantitatives et qualitatives recueillies depuis 25 ans au sud-est du Mali par le projet Slam-Suivi longitudinal au Mali. Les migrations adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The study of union breakdown requires data on marital histories, but this kind of data has been rarely collected in West African countries. In some research the longitudinal approach to studying unions has been adopted; at the national level (Gnoumou Thiombiano and Legrand 2014), in cities (Marcoux 1997;Antoine and Dial 2005;Antoine 2006), and on specific populations (Hertrich 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study of union breakdown requires data on marital histories, but this kind of data has been rarely collected in West African countries. In some research the longitudinal approach to studying unions has been adopted; at the national level (Gnoumou Thiombiano and Legrand 2014), in cities (Marcoux 1997;Antoine and Dial 2005;Antoine 2006), and on specific populations (Hertrich 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contexts where women’s social position is primarily determined by marriage and family relationships and where employment options outside subsistence agriculture are very limited, women may strongly prefer to stay married, and thus may seek to influence men’s behavior within a marriage rather than leave the marriage. Consistent with this possibility, some research in sub-Saharan Africa has found that women’s autonomy is associated with lower divorce rates (e.g., Hertrich, 2014). This association, however, is contingent on the marital partners’ communication.…”
Section: Theoretical Frameworkmentioning
confidence: 79%
“…Consistent with this possibility, some research in sub-Saharan Africa has found that women's autonomy is associated with lower divorce rates (e.g., Hertrich, 2014). This association, however, is contingent on the marital partners' communication.…”
Section: The Role Of Women's Autonomymentioning
confidence: 88%